Geographical Analysis of Pollution Types (Noise, Visual, Solid waste) in the Commercial Center of Soran City - Rizgar M. U. Hanaraye; Kamaran W. Mahmood; Shwan A. Ali (Zanco Journal of Humanity Sciences)
Because of its various functions, the city of Soran has become a significant urban center in the mountainous territory of the Governorate of Erbil, and has become populated by a lot of people, particularly in the commercial center that grows up day by day, and gave this place independently personal separately from the other parts of the city in terms of characteristics. One of these attributes is the environmental problems that may not occur at the same rate in the rest of the city, such as pollution. The study aims to determine the types of pollution such as noise, visual and solid waste in the commercial center of the city of Soran. The hypothesis is that these environmental pollutions concentrates in the commercial center and the main reason for that is the commercial function besides lack of planning process. The study divided into three sections, study area, methods, and results and discussion, and ended with conclusions and recommendations.